The impact of tungsten and tungsten transport on H-mode plasmas, experiments and modeling - C. Angioni (Nuclear Fusion)
Tungsten has been identified and shown to have several very good properties which are necessarily required by the plasma facing material of a magnetic fusion reactor. At the same time, particularly in the relevant range of temperatures for fusion reactions, it is one of the most strongly radiating elements on Earth. This has strong implications in the operation, the properties and the performances of plasmas which are obtained with tungsten plasma facing components, particularly in H-mode conditions. In this paper these aspects are reviewed, emphasizing how strongly the tungsten behavior connects the conditions at the walls with the dynamics of the core plasma. As a consequence of this, the operation with tungsten walls, particularly in H–mode plasmas, provides a paradigmatic example of the challenges which are caused by the need of integrating often competing requirements of good core performance and viable exhaust at the edge.